P25 Relationships between airway hyper-responsiveness, airway inflammation and airway calibre in asthmatic subjects. (16th November 2010) - Short, PM; Lipworth, SIW; Lipworth, BJ
Abstract : Introduction and Objectives: We wished to examine therelationships between inflammation (FENO ), methacholine challenge (AHR) and airway calibre (FEV1%) in a group of mild-to-moderate asthmatics. Methods: We searched our patient database forthose individuals with a known diagnosis of asthma who had a methacholine PC20 ≤ 8 mg/ml. Data regarding FEV1%, FENO, skinprick and methacholinePC20 were collected and divided into groups based upon AHR: severe (<0.5 mg/ml), moderate (>0.5–2 mg/ml) and mild (>2–8 mg/ml); and FENO : low (<25 ppb), medium (25–50 ppb) and high (>50 ppb). Results: We identified 208 who had a known diagnosis of asthma, a methacholinePC20 ≤8 mg/ml, as well as FENO and skin prick testing. Mean age (SEM) was 41.1 (1). There was an 8.5% difference in FEV1% between groups A and C, (95% CI (2.6% to 14.4%) p=0.002) and a 29% difference for FENO between groups A and C, (95%CI (2% to 48%) p=0.034). There was a 1.29 doubling dilution difference in methacholinePC20 (95%CI (0.26 to 2.33) p= 0.009) between groups D and F. There was no significant difference between FEV1% when grouped by FENO (See Abstract P25 Table 1 ). Applying multiple stepwise linear regression showed that FENO and FEV1% were both significant predictors of methacholine PC20 (p= 0.002, p<0.001). Only methacholine PC20 was a significant predictor of FENO (p=0.002). Conclusion: Our study has highlighted the disconnect between airway inflammation and airway calibre, whilst showing a significant relationship between AHR versus airway calibre and inflammation. Thus, whilst relationships exist between these independent outcomes, the lack of complete concordance highlights the important role that each contributes to the assessment of the asthmatic individual.